Theories of Change in Reality: Strengths, Limitations and Future Directions - Koleros, Andrew; Adrien, Marie-Hélène; Tyrrell, Tony (Routledge, 2024)
For over 50 years, evaluators have used theories of change to articulate the causal logic underpinning how an intervention is intended to bring about a desired change. From its origins in programme evaluation, the approach has been adopted more widely for purposes from program design to program management. As theories of change continue to be used for multiple purposes, it is an opportune moment for the evaluation community—where the approach originated—to provide their perspective on the strengths and limitations of the approach and its future directions. To provide these perspectives, we asked nearly 30 of the world’s leading evaluators and programme theorists to provide a short essay on the past, present, and future of theories of change. This book presents their insights organized into five main themes: the use of theories of change in broader public policy contexts; using theories of change to establish causality; developing theories of change reflective of multiple stakeholder perspectives; using theories of change to understand wider societal change processes; and applying theories of change approaches for multiple purposes. By sharing these diverse perspectives, the book aims to both provide evaluators and emerging programme theorists with critical perspectives to inform future practice. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.

Conclusions around theories of change in reality - Koleros, Andrew; Adrien, Marie-Hélène; Tyrrell, Tony (Theories of Change in Reality, 2024)
This book sets out the responses from a group of international practitioners and experts to three questions posed by the editors around how they are using theories of change in their work, what they have found to be the limits of their use, and what further adaptations they feel are needed so that theories of change remain relevant and useful in the future. The responses we received are, given the diversity of the contributors, understandably diverse with reference to perspective, emphasis, and the context within which theories of change are used. Broadly, their perspectives indicate that theories of change have long represented a valuable approach in both programme planning as well as in evaluation design and practice; however, the authors also make clear that theories of change are often misunderstood and misused. In particular, the authors draw attention to the use of theories of change as a static product rather than an iterative, inclusive process that recognises the centrality of multiple stakeholder perspectives in evaluation design and practice. The authors also highlight the challenges involved in the application of theories of change in contexts defined by heightened complexity.